Isolation and characterization of lignin‐degrading bacteria from rainforest soils1. (9th February 2013) - Huang, Xing‐Feng; Santhanam, Navaneetha; Badri, Dayakar V.; Hunter, William J.; Manter, Daniel K.; Decker, Stephen R.; Vivanco, Jorge M.; Reardon, Kenneth F.
Abstract The deconstruction of lignin to enhance the release of fermentable sugars from plant cell walls presents a challenge for biofuels production from lignocellulosic biomass. The discovery of novel lignin‐degrading enzymes from bacteria could provide advantages over fungal enzymes in terms of their production and relative ease of protein engineering. In this study, 140 bacterial strains isolated from soils of a biodiversity‐rich rainforest in Peru were screened based on their oxidative activity on ABTS, a laccase substrate. Strain C6 (Bacillus pumilus) and strain B7 (Bacillus atrophaeus) were selected for their high laccase activity and identified by 16S rDNA analysis. Strains B7 and C6 degraded fragments of Kraft lignin and the lignin model dimer guaiacylglycerol‐β‐guaiacyl ether, the most abundant linkage in lignin. Finally, LC–MS analysis of incubations of strains B7 and C6 with poplar biomass in rich and minimal media revealed that a higher number of compounds were released in the minimal medium than in the rich one. These findings provide important evidence that bacterial enzymes can degrade and/or modify lignin and contribute to the release of fermentable sugars from lignocellulose. Biotechnol. Bioeng. 2013; 110: 1616–1626. © 2013 Wiley Periodicals, Inc.